Application of the Game Analytical Game (GAG) Training Model to Pariaman City Football Coaches - Aldo Naza Putra; Ridho Bahtra; Frizky Amra (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2023)
Football is a game sport that requires good basic technical skills. Good basic techniques will support players to be able to take many actions in a match. Choosing the right training model will encourage the creation of a structured and directed training process. Based on the analysis of needs in the field, it is known that the trainer provides training based on experience as a player, without any guidelines, so that the lack of knowledge of the trainer about variations in training can eventually lead to boredom, so that the basic technique does not improve. To overcome these problems, soccer coaches need to be given various appropriate training models. The approach method used is 1) Workshop to share understanding in preparing appropriate training programs to improve basic techniques, 2) Implementation in the field to understand more deeply how to apply the Game Analytical Game training model 3) Follow-up discussions according to the context of monitoring and evaluation. The result of this activity is the coach's ability to create appropriate and varied training programs to improve basic football technical skills.